(3THcGJ GdJhGUd GdGLJeGYi h JfejI Gdbje GdGLJeGYjI dOi WdGH GdeQMdI GdKGfhjI HOhdI GdchjJ (B/ s - (3efi SYhO YHOGdYRjR GdbWGfs; (3SGei eMeO fUGQ (B: s; (3haGA CMeO CHh RjO (B: s ((3GdbGgQI (B: s (3efi SYhO YHOGdYRjR GdbWGf (B: s, 2015)
(3JgOa GdOQGSI Edi GdJYQa Ydi THcGJ GdJhGUd GdGLJeGYi h JfejI Gdbje GdGLJeGYjI dOi WdGH GdeQMdI GdKGfhjI HOhdI GdchjJ(B: (3h EjVGM hGbY GSJNOGe THcGJ GdJhGUd GdGLJeGYi ef bHd WdGH GdeQMdI GdKGfhjI HOhdI GdchjJ(B: (3h GdcTa Yf CcKQ hSGFd GdJhGUd GdGLJeGYi GSJNOGeG Hjf WdGH GdeQMdI GdKGfhjI HOhdI GdchjJ(B: (3h GdcTa Yf Gdbje GdGLJeGYjI GdJi jecf Cf JSGYO THcGJ GdJhGUd GdGLJeGYi Ydi JfejJgG dOi WdGH GdeQMdI GdKGfhjI ef hLgI fXQ GdWdGH h QDSGA h GdeOjQjf(B: (3h JbOje JUhQ ebJQM dJfejI Gdbje GdGLJeGYjI dOi WdHI GdeQMdI GdKGfhjI HOhdI GdchjJ ef NdGd JaYjd THcGJ GdJhGUd GdGLJeGYi ef hLgI fXQ LejY CaQGO GdYjfIs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdOQGSGJ GdYdjG ddJQHjI (B- (3bSe CUhd GdJQHjIs
(3UOQ GjVG cbQU eOeLs
Keywords: (3JfejI Gdbje GdGLJeGYjIs; (3THcGJ GdJhGUd GdGLJeGYis; (3WdGH GdeQMdI GdKGfhjIs